Aberrant methylated EDNRB can act as a potential diagnostic biomarker in sporadic colorectal cancer while KISS1 is controversial. Issue 5 (3rd September 2017) - Mousavi Ardehaie, Reza; Hashemzadeh, Shahriar; Behrouz Sharif, Shahin; Ghojazadeh, Morteza; Teimoori-Toolabi, Ladan; Sakhinia, Ebrahim
ABSTRACT: Cancers are among the most serious threats of human health worldwide. Survival and mortality rates of colorectal cancer (CRC) strongly depend on the early diagnosis. The aberrant methylation pattern of genes as a diagnostic biomarker can serve as a practical option for timely detection and contribute subsequently to the enhancement of survival rate in CRC patients, since methylation changes are not only frequent but also can occur in initial tumorogenesis stages. It has been indicated that EDNRB and KISS1 genes are hypermethylated through progression and development of CRC. In current study, after extraction of genomic DNA from 45 paired tumor and adjacent non-cancerous tissue samples and treatment with bisulfite conversion, the methylation status of EDNRB and KISS1 CpG rich regions were assessed quantitatively using MS-HRM assay to determine practicability of these aberrant methylations for diagnosis of sporadic CRC and its discrimination from corresponding normal tissues. The results showed that the methylation distribution differences, comparing tumor tissues with their adjacent non-cancerous tissues, were statistically significant in all selected locations within EDNRB gene promoter ( P < 0.001); they had also some correlations with tumor stage and grade. Nonetheless, methylation distribution in KISS1 gene CpG rich region revealed no statistically significant differences between CRC and adjacent non-cancerous tissues ( P = 0.060). Overall, it can be concluded that aberrant methylated EDNRB can be a promising potential diagnostic biomarker for CRC, while KISS1 is controversial and needs to be more investigated.